Pertanggungjawaban Notaris Penerima Protokol Terhadap Protokol yang Disimpannya Setelah Berakhir Masa Penyimpanannya - Jannnah, Miftahul (Recital Review, 2026)
This research was conducted to analyze the liability of notaries who keep notary protocols after the end of their storage period. The formulation of the problem from this study is how the notary is accountable for the notary protocol that he keeps after the end of his storage period. The results of this study conclude that the responsibility of the notary recipient of the protocol to the notary protocol that he keeps after the end of the storage period is to store, maintain, and maintain so that the Protocols are stored safely so that they are not easily damaged and lost because the Notary Protocol is a state archive that must remain. The role of the Regional Supervisory Council has not run efficiently and effectively because of the constraints of facilities and infrastructure for storing notary protocols.